El enfoque de competencia y los procesos educativos en la Institución Universitaria Antonio José Camacho (UNIAJC): una lectura crítica y una hipótesis de trabajo curricular innovadora y alternativa a la concepción y práctica en uso (2020)
In this second part of the article, the reader will find the UNIAJC's own competence approach, treated with the emphasis placed both on the relationship of unity, diversity and complementarity of the curriculum theory/curricular practice, as well as on the local coherence of the entire proposal; which includes the concepts of competence and professional competence. Likewise, from a critical and self-critical reflection, it is impelled to examine as a necessity, the accentuated implications of the Competency Approach assumed by the Institution as an innovative curricular posture that entails significant transformations in the conceptions and formative practices, in what it is our responsibility, located in the context of higher education, at all levels and academic, planning, administrative and operational levels; among them, everything related to the evaluation, which must change in a remarkable way.